Indonesian Halal Pharmaceutical: Challenges And Market Opportunities - Yedi Herdiana; Taofik Rusdiana (Indonesian Journal of Pharmaceutics, 2021)
The halal food market has grown worldwide, including the shift from food to other products, including halal pharmaceuticals (HPC).  The growth followed by the abundance of literature has been on halal, especially pharmaceuticals. Muslim consumers need halal certification (HCT) on medicines to ensure that they do not consume or use products or services that are not halal. The government must guarantee to Muslim consumers that consumer goods or services circulating in the community are truly halal. The halal label itself will increase consumer confidence, expand the reach of the global halal food market, and increase the marketability of products in the market. Indonesia, which is predominantly Muslim, is considered a long extension in implementing HP until 2034. Different attitudes are shown by several countries with large non-Muslim majority populations but are very concerned about the implementation of HPC. The accelerated growth of knowledge of halalness, impact social media, will push the industry to implement HPC. In this review, we will discuss critical players in implementing HPC, including the ingredients that have been widely used but still doubt their halalness and what they are used for in the pharmaceutical industry. This knowledge is essential for industry and researchers to build safer alternative materials.Keywords: Halal, Indonesia,  Muslim, Halal Pharmaceutical, Halal Certification.